Customer Engagement and Relationship Management's Effects on Business Performance in Digital Banks - Elvera Elvera; Sastra Mico (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
CRM (Customer Relationship Management) is a tool used by businesses to understand customer demands and behavior in order to deliver the best possible customer service, preserve current relationships, and boost business success. In order to understand how customer engagement and customer relationship management affect business success in digital banks, a study was done. The research population consists of 3.9 million digital bank users in total. 400 samples were acquired after simple random sampling, which was then used to calculate the Slovin formula at an acceptable level of 5%, and multiple linear regression analysis was performed. In this study, there are two independent variables: customer engagement and customer relationship management. The dependent variable is business performance. The results of this study suggest a tight connection between customer relationship management and customer engagement and the operational success of digital banks. The purpose of this research is to present data that the management of digital banks can utilize to make various decisions.